Assisted return programmes across Europe – Mapping an increasingly obscure landscape - Lukas M. Fuchs (International Migration, 2025)
Amidst an increasing popularity of Assisted Return (AR) programmes amongst European states, on the one hand, and criticism pertaining to their voluntary and humanitarian nature, on the other hand, this paper maps AR programmes across Europe. It contains a first comprehensive overview of 45 ongoing AR programmes across 27 countries in the European Economic Area (EEA) and outlines their commonalities and specificities along five categories: (1) clarity and reliability of available information, (2) involved actors, (3) targeting, (4) offered support and (5) accountability and empirical knowledge production. The mapping finds relevant differences in programme design according to the centralization and distribution of responsibilities between state actors, IOM and NGOs. Similarly, programmes vary according to their target groups ranging from highly specific (e.g. for victims of trafficking) to those addressing virtually all non-EU citizens. Another marked distinction concerns the labelling as either assisted return or return & reintegration programme, which may be in contrast to the amount, scope and timing of the offered support. The findings and identified knowledge gaps are discussed in relation to relevant literature to contextualize our understanding of the proliferation of AR activities and formulate recommendations for future research.
Keywords: 300